Reviews. Issue 1 (1st June 2019) - Jochum, Elizabeth; Stout, Graeme; Bergen-Aurand, Brian
Abstract : Jennifer Rhee, The Robotic Imaginary: The Human and the Price of Dehumanized Labor (Minneapolis: University of Minnesota Press, 2018). 240 pp., ISBN: 978151790298 (paperback, 27) Soraya Murray, On Video Games: The Politics of Race, Gender and Space (New York: I. B. Tauris, 2018). xv + 315pp., ISBN: 9781786732507 (PDF eBook, 82.50) Ari Larissa Heinrich, Chinese Surplus: Biopolitical Aesthetics and the Medically Commodified Body (Durham, NC: Duke University Press, 2018). 264 pp., ISBN: 9780822370536 (paperback, 25.95)